2017
DOI: 10.1111/jth.13746
|View full text |Cite
|
Sign up to set email alerts
|

Safety of multidetector computed tomography pulmonary angiography to exclude pulmonary embolism in patients with a likely pretest clinical probability

Abstract: Background In patients with suspected pulmonary embolism (PE) classified as having a likely or high pretest clinical probability, the need to perform additional testing after a negative multidetector computed tomography pulmonary angiography (CTPA) finding remains a matter of debate. Objectives To assess the safety of excluding PE by CTPA without additional imaging in patients with a likely pretest probability of PE. Patients/Methods We retrospectively analyzed patients included in two multicenter management o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…Another available benchmark is follow-up of patients for recurrence of PE as a predictor of false negative results. An equivalent of sensitivity was calculated on the basis of a 3-month follow-up in 14,545 patients where PE was excluded by CTPA [48, 94, 95, 133138] and in another 1865 patients where this was done by V/P SPECT [52, 74, 75, 139]:…”
Section: Additional Considerationsmentioning
confidence: 99%
“…Another available benchmark is follow-up of patients for recurrence of PE as a predictor of false negative results. An equivalent of sensitivity was calculated on the basis of a 3-month follow-up in 14,545 patients where PE was excluded by CTPA [48, 94, 95, 133138] and in another 1865 patients where this was done by V/P SPECT [52, 74, 75, 139]:…”
Section: Additional Considerationsmentioning
confidence: 99%
“…Two studies used a single and multidetector scanner and in five studies the type of scanner was not specified. CTPA was most commonly performed as part of a diagnostic algorithm in patients with positive D-dimers or a non-low pretest clinical probability (n = 12) [6,7,21,23,24,26,29,31,[38][39][40][41]. In five studies, venous ultrasound was systematically performed as part of the diagnostic algorithm [21,25,27,33,36].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…
and † †Service de tive studies are required to validate the appropriate diagnostic algorithm for this subgroup of patients.Computed tomography angiography in pulmonary embolism 1109 CDR, clinical decision risk score; CT, computed tomography; CTPA, computed tomographic pulmonary angiography; PE, pulmonary prevalence; MSCT, multi-slice computed tomography; DVUS, deep venous ultrasound; CTV, venous-phase multidetector computed tomographic venography; PA, pulmonary angiography; V/Q, ventilation-perfusion lung scintigraphy.*Data from the two Righini studies [7,37] were extracted from the data presented in another article [41]
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonary embolism was excluded with CTPA in 37% of patients with likely clinical probability, and the 3-month VTE risk was 0.6%, indicating that a negative CTPA safely excludes PE in this patient group. 47 The prevalence of PE in patients presenting with syncope has been highly debated this year, following the PESIT trial, reported last year, 39 describing a 17% rate of PE in syncope cases referred to emergency rooms, after excluding cases with evident aetiology. A meta-analysis including 6608 emergency department patients and 975 patients hospitalized for syncope reported a PE prevalence <1%.…”
Section: Venous Thromboembolismmentioning
confidence: 99%